Sleep and the young athlete - Coel, R. A.; Pujalte, G. G. A.; Applewhite, A. I.; Zaslow, T.; Cooper, G.; Ton, A. N.; Benjamin, H. J. (Sports Health: A Multidisciplinary Approach, 2023)
Context: Sleep plays a vital role in cognitive and physical performance. Teenage athletes (ages 13-19 years) are considered especially at risk for disordered sleep and associated negative cognitive, physical, and psychosomatic effects. However, there is a paucity of evidence-based recommendations to promote sleep quality and quantity in athletes who fall within this age range. We performed a review of the literature to reveal evidence-based findings and recommendations to help sports instructors, athletic trainers, physical therapists, physicians, and other team members caring for young athletes provide guidance on sleep optimization for peak sports performance and injury risk reduction.